Inward Internationalization of African-Ethnic Restaurants: The Role of Managerial Dynamic Capabilities - Otengei, Samson O.; Bakunda, Geofrey; Ngoma, Mohammed; Ntayi, Joseph M.; Munene, J. C. (Advances in Hospitality and Tourism Research, 2016)
This paper empirically tests the link between cultural orientation, market orientation, service innovation capabilities of owner-managers and the level of inward internationalization of African-ethnic restaurants. Data were obtained from 201 African-ethnic restaurants. A two-step approach was used, i.e. (i) a confirmatory factor analysis (CFA) to generate a measurement model; and (ii) a structural equation model (SEM) to test the hypotheses. All the predictor variables are positively and significantly related to the degree of inward internationalization and the relationship is strong enough to cause a 41 per cent variance. Since it is cross-sectional in design, the study cannot be fully relied upon to draw inferences regarding causality among the variables. The results suggest that owner-managers who develop the three capabilities succeed in enhancing inward internationalization.
Keywords: Cultural orientation; Market orientation; Service innovation; Inward internationalization